Isolasi dan Identifikasi Bakteri Probiotik Dari Usus Udang Windu (Penaeus monodon) Berdasarkan Sekuens Gen 16S rDNA - Seprianto S; Feliatra F; Titania T Nugroho (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2017)
Probiotics are living microorganisms that have beneficial effect on the host by improving the balance of bacteria in the intestines. This research was aimed to determine the diversity of bacteria that live in digestion of the shrimp and molecular characteristics along with to observe phylogenetic relationships among the bacteria identified based on sequence16S rDNA. The bacteria were isolated from intestine of the Tiger prawn (Penaeus monodon) obtained from fishpond at BBPBAP Jepara. The analyzed result of 16S rDNA shown that three bacterial species were potential as probiotic. These bacteria grow well at pH 2 and this indicates one of probiotic bacteria characteristic. Among the three isolates, two isolates i.e. SP2 and SU isolates were phylogenetically closely related to Bacillus bataviensis strain CCGE2059 (EU867382.1) with 97% homology. While the SWU Isolate is most likely a new species of Caulobacter sp. (AJ227775.1). The SWU isolates were phylogenetically one ancestor with the Chromobacterium violaceum.